Development of the technique of nondestructive testing of heterogeneous dielectric materials based on utilization of the mechanoelectric transformation phenomenon - Fursa T. V. Tatyana Viktorovna (2010, 2010)
Defects of different types and sizes in a material are shown to result in variations in thespectral characteristics of electric responses to pulsed mechanical excitation of heterogeneous mate_rials. General regularities reside in an increase in the size and concentration of defects that yields adecrease in the magnitude and quality factor of the principal spectral maximum and variations in thespectral composition of the electric response